DIVERSITY OF VISITOR INSECTS IN CAYALY CABE (Capsicum frutescens) GARDEN ON KARST LAND, GUNUNG KIDUL, YOGYAKARTA - Handru, Alan; Sidiq, Muhammad Fajar; Avianto, Yovi; Noviyanto, Amir; Jaya, Galang Indra; Putri, Diyona (Universitas Veteran Bangun Nusantara, 2025)
This study aims to identify and analyse the diversity of insect visitors to the cayenne pepper (Capsicum frutescens) garden in the karst area of Gunung Kidul, Yogyakarta. The method used was purposive sampling method by direct capture. The data collected were analysed by Shannon-Wiener diversity index. The conclusion of this study is that there is a diversity of visitor insects categorised as medium (H'=1.7) in the cayenne pepper garden in the karst area of Gunung Kidul, Yogyakarta. This insect diversity can help in the process of pollination and natural pest control in cayenne pepper plants in the karst area. Understanding the diversity of these insects is important for environmental conservation and sustainable agricultural management, especially in karst areas.